Exploring prenatal care experiences in Ontario, Canada: An equity-oriented qualitative study - Zeenat Ladak; Muzzammil Hooda; Tolulope Ojo; Daphne To; Rochelle Simmons; Jennifer Shuldiner; Ummul-Kiram Patrawala; Emily Nicholas Angl; Celia Laur; Mehdiya Hemani; Olesya Falenchuk; Richard Volpe; et al. (PLoS ONE, 2026)
Introduction The extent to which prenatal care is equity-oriented significantly influences patient satisfaction, care-seeking decisions, and health outcomes for both parent and newborn. The social determinants of health shape care experiences, disproportionately affecting marginalized populations (e.g., low-income, rural, racial minorities). This study explores prenatal patients’ care experiences and examines the impact of health inequities on these experiences. Methods This patient-partner-oriented, cross-sectional, qualitative study was guided by Cochrane’s PROGRESS-Plus equity framework and carried out using a pragmatist paradigm. Purposeful, maximum variation sampling recruited individuals in Ontario, Canada who had been pregnant or experienced pregnancy loss within the last 12 months. Participants completed a 5-minute sociodemographic survey and a 1-hour semi-structured interview on their prenatal care experiences and equity impacts. Analysis included descriptive statistics, and inductive and deductive content analysis. Results This study included 18 participants, half identifying as racial minorities. All participants interacted with a healthcare professional during pregnancy; most were followed by a primary care physician (n = 16), half by an obstetrician (n = 9), half by a nurse (n = 9), and/or eight by a midwife. Qualitative findings included experiences in accessing care ranging from feelings of powerlessness to continuity of care challenges, influenced by geographical and financial barriers. In addition, experiences of patient-centered care encompassed empathetic practitioners, validation of concerns, and power dynamics, influenced by discrimination and advocacy for personalized support. Conclusions This study offers an in depth understanding of experiences that have the potential to improve pregnancy care including targeted access to health services in remote areas, diminishing patient-provider hierarchies, culturally-sensitive care approaches for trust-building, and community engagement. Findings can inform healthcare professionals and policymakers about patients’ expectations of equity-oriented prenatal care.